Splenic Artery Embolization for Nonocclusive Hepatic Artery Hypoperfusion - Jenner, Zachary B.; Di Geronimo, Ryan T.; Molano, Pilar Bayona; Pillai, Rex M. (Digestive Disease Interventions, 2020)
Various minimally invasive, surgical, and laparoscopic interventions are performed for treatment and management of splenic artery steal syndrome in liver transplant and cirrhotic patients. Common approaches include splenic artery banding, ligation, stenting, and embolization to increase hepatic arterial flow. Splenic artery embolization has undergone further development to facilitate timely diagnosis, increase efficacy, decrease adverse outcomes, and improve patient selection. We review the current diagnostic modalities and technical advancements of splenic artery embolization to improve hepatic arterial perfusion in patients with splenic artery steal syndrome.
Keywords: splenic artery steal syndrome; liver transplant; cirrhotic patient; nonocclusive hepatic artery hypoperfusion